The effectiveness of some pesticides in combating peach leaf curl disease caused by the fungus Taphrina deformans on almond trees - احمد, اماني; عبد الرحمن خفتة (Latakia University Journal -Biological Sciences Series, 2024)
The disease research was carried out in the village of Al-Qusaybiyah (Sheikh Badr), Tartous Governorate, during the autumn of 2021 and the spring of 2022, for the purpose of testing three fungicides: difenoconazole, copper oxychloride, and captan in combating the fungus Taphrina Deformans, which causes almond leaf curl, compared to the control. The recommended concentration of field-tested pesticides was used at a rate of three replicates per treatment and at a rate of five trees per replicate. According to a completely randomized block design. The results of the study showed that the spraying process with the tested pesticides was effective in reducing the incidence of leaf curl disease on almonds when sprayed in the fall compared to the control. The pesticide difenoconazole gave the highest effectiveness in the spring and fall experiments, 80.82% and 82.75%, respectively, while the pesticide Captan was the least effective was 58.64% and had no effect when applied in the spring.